Propagation of Perturbations in Quasilinear Multidimensional Parabolic Equations with Convective Term - Sapronov, D. A.; Shishkov, A. E. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We establish estimates for the initial evolution of the supports of solutions of a broad class of quasilinear parabolic equations of arbitrary order that have the structure of the equation of strong nonlinear convective diffusion.